Geographic Information System Design for Bridge Management in Brebes Regency - Abdulloh Badruzzaman; Yana Hendriana (Jurusan Teknik Informatika, 2021)
Purpose: geographic information system (GIS) design to monitoring and management of bridges that have geographic references, as well as a tool for planning activity programs (maintenance, rehabilitation, strengthening or replacement) of bridges.Design/methodology/approach: waterfallFindings/result: web-based geographic information system (GIS) for bridge management in Brebes RegencyOriginality/value/state of the art: this research does not only focus on site search as the main strength of GIS but maximizes bridge inspection activities as an important part of the bridge management system as a tool for planning bridge construction and maintenance activities